Analisis Pengaruh Penggunaan Instagram, Pengalaman Praktik Kewirausahaan, Dan Hasil Belajar Kewirausahaan Terhadap Minat Berwirausaha Online - Kurniawan, Ignatius Soni (AKMENIKA, 2018)
This research is aimed to examine the effect of instagram use, online entrepreneurial practice experience, and online entrepreneurial learning outcome on online entrepreneurial intention. A number of 84 students of Management Department, Economic Faculty of Universitas Sarjanawiyata Tamansiswa were asked to fill in the questionnaire. This study findings show that the use of instagram is not significantly affect online entrepreneurial intention, on the other way partially online entrepreneurial practice experience and online entrepreneurial learning outcomes are significantly affect online entrepreneurial intention.